The perfect guests [large type] - Rous, Emma (Thorndike Press, 2021)
You are cordially invited to play a game at Raven Hall... When Beth was fourteen, she was invited into Raven Hall, a rambling, isolated manor house in the English countryside. The family who lived there were warm and welcoming, and Beth soon became firm friends with their daughter, Nina. At times, Beth even felt like she was truly part of the family... But then they asked her to play a very strange game - and nothing was the same again. Now, after years of abandonment, Raven Hall has been restored to its former glory and is playing host to an evening of murder mystery... But why does the tragic past of this imposing house seem to have such a hold on everyone? Is this really just a game, or a murder mystery for real? The guests are about to find out - with devastating consequences.